2013
DOI: 10.1038/ngeo1892
|View full text |Cite|
|
Sign up to set email alerts
|

Low simulated radiation limit for runaway greenhouse climates

Abstract: Terrestrial planet atmospheres must be in long-term radiation balance, with solar radiation absorbed matched by thermal radiation emitted. For hot moist atmospheres, however, there is an upper limit on the thermal emission which is decoupled from the surface temperature. If net absorbed solar radiation exceeds this limit the planet will heat uncontrollably, the so-called "runaway greenhouse". Here we show that a runaway greenhouse induced steam atmosphere may be a stable state for a planet with the same amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
261
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(299 citation statements)
references
References 39 publications
32
261
6
Order By: Relevance
“…Next, we compared the code output with runaway greenhouse calculations for Earth (Goldblatt et al 2013). Figure 3 shows the results of this intercomparison.…”
Section: Line-by-line Climate Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, we compared the code output with runaway greenhouse calculations for Earth (Goldblatt et al 2013). Figure 3 shows the results of this intercomparison.…”
Section: Line-by-line Climate Modelmentioning
confidence: 99%
“…Abundances of these elements are assumed to be the same as for the Earth's Figure 3. Outgoing longwave radiation from the line-by-line radiative-convective model (red) vs. results produced using the SMART code detailed in Goldblatt et al (2013). In each case, the atmospheric composition is 100% H 2 O, the assumed surface temperature is 300 K, and the atmospheric temperature profile follows the H 2 O saturation vapour pressure curve.…”
Section: Thermal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…1 dominated by water vapor, and an extreme form of water vapor feedback causes the OLR to asymptote to a limiting value, which I prefer to call the Kombayashi-Ingersoll (K-I) limit, in honor of the investigators who first recognized the significance of a limiting OLR for the evolution of the climate of Venus (this is referred to instead as the SimpsonNakajima limit in ref. 6). If the limiting solar absorption allowing for cloud dissipation was to lie above the K-I limit, then the Earth would be subject to runaway warming and succumb to the fate of Venus if the temperature were ever made warmer than state D. Although we are protected from runaway by water vapor subsaturation and cloud albedo in the present climate (and evidently in past hothouse climates as well), the disconcerting possibility that present Earth conditions could support a runaway as an alternate climate state has received support from recent revisions in calculations of the limiting infrared and solar fluxes (6, 7).…”
mentioning
confidence: 99%
“…The classical runaway greenhouse limit for a water atmosphere is approximately 300 W m −2 [10,11]. Recently, using more complete opacity data for hot H 2 O, Goldblatt et al [12] found 280 W m −2 for this limit. By vaporizing the current ocean volume, the surface could heat to more than 1500 K. With stronger opacity sources, it could become much hotter, and to current knowledge there is little to constrain the upper bound.…”
Section: Early Atmospheric Behaviourmentioning
confidence: 99%